2005
DOI: 10.1111/j.1365-2966.2005.08763.x
|View full text |Cite
|
Sign up to set email alerts
|

Radiative feedback from quasars and the growth of massive black holes in stellar spheroids

Abstract: We discuss the importance of feedback via photoionization and Compton heating on the coevolution of massive black holes (MBHs) at the centre of spheroidal galaxies, and their stellar and gaseous components. We first assess the energetics of the radiative feedback from a typical quasar on the ambient interstellar medium (ISM). We then demonstrate that the observed M BH -σ relation could be established following the conversion of most of the gas of an elliptical progenitor into stars, specifically when the gas-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
327
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 219 publications
(332 citation statements)
references
References 41 publications
5
327
0
Order By: Relevance
“…To keep the problem tractable, we estimate the net heating/cooling function by the value of the cooling function under steady-state conditions (in which case its values match those of the heating function). For solar metalicity, optically-thin gas exposed to a type-I quasar continuum (Sazonov et al 2005), the heating rate does not have a strong dependence on the temperature, varying by a factor of order unity in the range 10 4 < T c < 10 6 K, so that an adequate approximation for our purpose is…”
Section: Applications To Astrophysical Systemsmentioning
confidence: 99%
“…To keep the problem tractable, we estimate the net heating/cooling function by the value of the cooling function under steady-state conditions (in which case its values match those of the heating function). For solar metalicity, optically-thin gas exposed to a type-I quasar continuum (Sazonov et al 2005), the heating rate does not have a strong dependence on the temperature, varying by a factor of order unity in the range 10 4 < T c < 10 6 K, so that an adequate approximation for our purpose is…”
Section: Applications To Astrophysical Systemsmentioning
confidence: 99%
“…It is believed that massive black holes play an important role in the formation and evolution of galaxies, and the growth of the BH and bulges must be linked to the same physical processes; this results in BH masses that are related to the properties of host galaxies (Silk & Rees 1998;Haehnelt & Kauffmann 2000;Adams et al 2001;Merritt & Poon 2004;Sazonov et al 2005). Graham et al (2001) and Marconi & Hunt (2003) have shown that when bulge parameters are measured with sufficient accuracy using the technique of bulge-disk decomposition, the resulting scatter in the -L relation is compa-M BH rable to that in the -j relation (see also Graham 2007).…”
mentioning
confidence: 99%
“…After several billion years it would exceed a few percent of the Eddington rate where it likely changes to a radiatively efficient accretion state (Gallo et al 2003;Maccarone 2003;Falcke et al 2004;Wu & Cao 2008). Depending on the broadband spectrum of the quasar 8 and the gas temperature of the cluster, it might either lead to inverse Compton cooling (Fabian & Crawford 1990), which decreases the gas temperature and would stimulate even higher accretion rates, or to Compton heating (Sazonov et al 2004(Sazonov et al , 2005. Interestingly, powerful quasars with luminousities around L ≈ 10 47 −10 48 erg s −1 (comparable to our model predictions) are reported to be located in the Phoenix (Ueda et al 2013) and CL1821+643 cluster (Walker et al 2014).…”
Section: Smbh Runaway Growthmentioning
confidence: 99%